DARMA - INFORMATION SYSTEM FOR ACCESSING LHC DATA WITHIN THE ALICE EXPERIMENT AT CERN - Ján JADLOVSKÝ; Milan TKÁČIK; Slávka JADLOVSKÁ; Michal PÁNIK (Acta Electrotechnica et Informatica, 2021)
The paper deals with the implementation of systems for remote data access in cooperation with the international laboratory CERN in Geneva. The first part discusses extensions of the DARMA information system for archive management. The main goal of this paper is to design and enhance the system with new functionalities and solve known shortcomings, and thus qualitatively increase the potential of the DARMA system in the context of the ALICE DCS (Detector Control System). The final part of the paper deals with the analysis of historical data and the design of a system for the anomaly and failure detection in the infrastructure of high voltage channels within the TRD detector (Transition Radiation Detector).